Work and work accidents in the flexible working regime: the Zonguldak hard coal basin case - Sarıkaya, İbrahim. (Thesis (M.A.) - Bogazici University. Atatürk Institute for Modern Turkish History, 2012., 2012)
This thesis examines the work accidents in subcontracted companies in the Zonguldak Hard Coal Basin in the period of the flexible working regime post 1980. For this purpose, first, the political economy of work accidents is examined and the impacts of the new working forms on work accidents under the flexible working regime are discussed. Second, an overview of the history of the Zonguldak Hardcoal Basin is given. In addition to this, the changing global political economy of the coal production is analyzed by developing a comparative perspective between the cases of England, the People's Republic of China, and Turkey. Third, the redevance system as a subcontracting practice is studied. Fourth, the main causes of the work accidents in subcontracted companies and informal pits are discussed. As a result, we conclude that the flexible working regime as one of the main pillars of neoliberalism has increased rate of the work accidents in the Zonguldak Hard Coal Basin.
Keywords: Coal miners -- Turkey -- Zonguldak.; Flextime -- Turkey -- Zonguldak.